Critical success factors for corporate social responsibility adoption in the construction industry in Malaysia - Zahidy, Anat Anaqie; Sorooshian, Shahryar; Zahidy, Abd Hamid (MDPI, 2019)
In the construction industry, corporate social responsibility (CSR) is increasingly valued as a strategic tool for business sustainable development and for addressing ethical issues. However, understanding the concept of CSR in the construction industry, and how to practice it, is limited. This study aims to explore and assess the factors critical to the successful adoption of CSR in the construction industry through the lens of critical success factors (CSFs) theory. Through a literature review, a list of potential factors that may theoretically have a major impact on CSR adoption in the construction industry was compiled as a proxy. Then, the potential factors were refined and validated by employing a Delphi technique. An expert panel of sixteen qualified Malaysian industry practitioners and academia was assembled. Results from three iteration rounds of the Delphi process depicted that successful adoption of CSR in practices depends upon eight CSFs including financial resources, top management support, managerial or internal skills on CSR, national economic growth, employees’ education and training on CSR, participation of key stakeholders in the CSR process, effective CSR communication, and organizational structure. This study contributes to the field by addressing a theme that has been covered less in literature. Knowing the CSFs for CSR adoption in advance could help the construction firms to successfully integrate CSR into business strategies and minimize the risk of failure. Policy-makers could also consider the findings when promoting the CSR agenda or development programs that adhere to the construction industry’s way forward. Although this study is particularly suited for the Malaysian context, nevertheless, the outcomes could shed some light upon the CSR initiative in other countries, since CSR adoption status in the construction industry overall does not significantly differ between countries.